Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Find all zeros of the polynomial [tex]\(2x^2 - 3x^3 + 6x - 2\)[/tex] if two of its zeros are [tex]\(\sqrt{2}\)[/tex] and [tex]\(-\sqrt{2}\)[/tex].

Sagot :

To find all zeros of the polynomial [tex]\( 2x^2 - 3x^3 + 6x - 2 \)[/tex] given that two of its zeros are [tex]\(\sqrt{2}\)[/tex] and [tex]\(-\sqrt{2}\)[/tex], we can use the fact that polynomials can be factored into linear factors corresponding to each root.

Given the zeros [tex]\(\sqrt{2}\)[/tex] and [tex]\(-\sqrt{2}\)[/tex], the polynomial can be expressed as follows:
[tex]\[ f(x) = 2x^2 - 3x^3 + 6x - 2 \][/tex]
[tex]\[ f(x) = (x - \sqrt{2})(x + \sqrt{2})(Ax + B) = (x^2 - 2)(Ax + B) \][/tex]

Expanding the product [tex]\((x^2 - 2)(Ax + B)\)[/tex]:
[tex]\[ (x^2 - 2)(Ax + B) = A x^3 + B x^2 - 2 A x - 2 B \][/tex]

We need this expansion to match our original polynomial [tex]\( -3x^3 + 2x^2 + 6x - 2 \)[/tex]. Matching coefficients, we get:
[tex]\[-3x^3 + 2x^2 + 6x - 2 = A x^3 + B x^2 - 2 A x - 2 B \][/tex]

Now, let's equate the coefficients of the corresponding powers of [tex]\( x \)[/tex]:

For [tex]\( x^3 \)[/tex]:
[tex]\[ -3 = A \][/tex]

For [tex]\( x^2 \)[/tex]:
[tex]\[ 2 = B \][/tex]

For [tex]\( x^1 \)[/tex] (linear term):
[tex]\[ 6 = -2A \][/tex]
Substituting [tex]\( A = -3 \)[/tex] here, we can check if this holds true:
[tex]\[ 6 = -2(-3) \][/tex]
[tex]\[ 6 = 6 \, \text{(True)} \][/tex]

For the constant term:
[tex]\[ -2 = -2B \][/tex]
Substituting [tex]\( B = 2 \)[/tex] here, we can check if this holds true:
[tex]\[ -2 = -2(2) \][/tex]
[tex]\[ -2 = -4 \, \text{(True)} \][/tex]

From this, we find that the correct coefficients [tex]\( A \)[/tex] and [tex]\( B \)[/tex] are:
[tex]\[ A = -3 \][/tex]
[tex]\[ B = 2 \][/tex]

So, the factorization of the polynomial is:
[tex]\[ f(x) = (x^2 - 2)(-3x + 2) \][/tex]

We can now solve for the remaining zeros by setting each factor to zero:

1. [tex]\( x^2 - 2 = 0 \)[/tex]
[tex]\[ x^2 = 2 \][/tex]
[tex]\[ x = \pm \sqrt{2} \][/tex]
These are the given zeros, [tex]\(\sqrt{2}\)[/tex] and [tex]\(-\sqrt{2}\)[/tex], which we already know.

2. [tex]\( -3x + 2 = 0 \)[/tex]
[tex]\[ -3x = -2 \][/tex]
[tex]\[ x = \frac{2}{3} \][/tex]

Thus, the zeros of the polynomial [tex]\( 2x^2 - 3x^3 + 6x - 2 \)[/tex] are:
[tex]\[ \sqrt{2}, -\sqrt{2}, \text{ and } \frac{2}{3} \][/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.